The Menu: Cultural Translation Analysis in a Culinary Movie - Nisak, Khoirotun; Ishlaiyah, Mazroatul (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
Translation that considers cultural context and terminology is essential for accurately conveying cultural understanding. An appropriate translation also helps to preserve the authenticity of meaning and cultural nuances within a text. As streaming services becoming more global and accessibility for different languages becoming increasingly important, this research examines how culinary cultural terms in the film The Menu are translated. The study focuses on accuracy, the techniques used in subtitle translation, and how domestication and foreignization strategies influence audience understanding and interpretation of cultural content. This study employs a descriptive qualitative method with data collection techniques in the form of document or text analysis, specifically focusing on the translation of culinary terms found in the film The Menu. In analyzing the data, the researchers apply Newmark’s (1995) theory of cultural terms to categorize cultural terms within the culinary context present in both the source and target language subtitles of the film. Additionally, Molina and Albir’s (2002) translation techniques are utilized to identify the translation techniques employed by the subtitle translator, while Venuti’s (1994) translation ideology is used to determine the ideology maintained by the translator based on the applied translation techniques. The study analyzed 50 culinary cultural terms found in the film. The study analyzed 50 culinary cultural terms found in the film. The findings indicate that foreignization is the dominant ideology, with literal translation as the most commonly used technique, followed by borrowing and established equivalents. While this approach preserves the authenticity of cultural terms and exposes Indonesian viewers to the original culinary concepts, it may also create challenges in comprehension, particularly when culturally specific terms lack direct equivalents in the target language. This research added to the understanding of subtitling practices and highlighted the need for translators to maintain a balance between cultural integrity and audience accessibility. A limitation of this study is the researcher's potential bias in interpreting the meanings.